Design and Development of a Web-Based Invitation and Gift Set Order Management Information System Using CodeIgniter 4 with the DevOps Method at PT Karya Cita Corellia - Zhafira, Aura Zahra; Rosliani, Elin Rosliani (Jurnal Accounting Information System (AIMS), 2026)
This study aims to design and build a website-based invitation and gift order management information system using the DevOps method as a software development approach. The system's main features include a client order form, a gift order form, and a client report management database. The implementation of the DevOps method enables a faster, more collaborative, and more predictable development cycle through the planning, coding, building, testing, release, deployment, operation, and monitoring phases. The result of this system design and development is a website that facilitates digital order entry, automatically presents client reports, and displays the company profile in a more professional manner. This system is expected to improve work efficiency and reduce errors in data processing.